Distance and proximity in Hubert Robert. (23rd September 2019) - Jones, Nathaniel B; Ryu, Sara
Abstract: This essay focuses on questions of distance and proximity, both chronological and spatial, in the painting of eighteenth-century French artist Hubert Robert. It argues that, through the manipulation of different modes of distance in his paintings, Robert sought to articulate an aesthetic attitude which highlighted the remoteness of the past at the same time as he brought it into dialogue with the present. This aesthetic of distance is variously enacted by Robert's pictorial reflections on the ancient Roman system of roads, the virtual creation and collection of antiquities, and the actual movement of the physical remnants of the ancient world. The result, the essay suggests, is that Robert's work straddles the border of fiction and reference to both acknowledge and deny the presentness of the past.